A tool to aid talking about dementia and dying: Development and evaluation - Stirling, C.; McInerney, F.; Andrews, S.; Ashby, M.; Toye, Christine; Donohue, C.; Banks, S.; Robinson, A. (Royal College of Nursing Australia, 2014)
Background: Health professionals often avoid talking about death and dying with patients and relatives, and this avoidance is compounded in cases of dementia by lack of knowledge of trajectory and prognosis. Unfortunately, this impacts on care, with many terminally ill dementia clients receiving inadequate palliation and excessive intervention at end-of-life. This study developed and evaluated a tool to facilitate conversations about death and dying in aged care facilities.Methods:This study utilised available best-practice evidence, feedback from aged care facility nursing and care staff and specialist input to develop the ‘discussion tool’, which was subsequently trialled and qualitatively evaluated, via thematic analysis of data from family interviews and staff diaries. The study was part of a larger mixed method study, not yet reported. The tool provided knowledge and also skills-based ‘how to’ information and specific examples of ‘what to say’.Results :The tool facilitated a more open dialogue between dementia palliation resource nurses (a role specifically developed during this project) and family members. Both resource nurses and family members gained confidence in discussing the death of their relative with dementia, and in relevant cases discussed specific decisions around future care. Family members and nurses reported satisfaction with these discussions.Conclusion: Providing specific skills-based support, such as the ‘discussion tool’ can help staff to gain confidence and change practice in situations where unfamiliar and uncomfortable practices might normally be avoided. As our populations age, health professionals will increasingly need to be able to openly discuss care options towards end-of-life.